Fear of Covid-19 contagion: The idiosyncratic effects of an aggregate pandemic shock - Junichi Kikuchi; Ryoya Nagao; Yoshiyuki Nakazono (Osaka University, Institute of Social and Economic Research (ISER), 2021)
We examine how the fear of COVID-19 contagion influences consumer expenditure patterns. We show that the consumption expenditure responses to the spread of the COVID-19 pandemic are significantly heterogeneous across generations. We find that the elderly spend less than the younger generation by at least 5% as COVID-19 spread. In fact, those aged above 60 significantly decreased their spending even on food and drink products by 13%. We also find that the elderly forgo shopping in favor of the younger generation. These heterogeneous responses are likely to be due to the fear of the COVID-19 infection.
Keywords: D12; E21; 330; COVID-19; consumption gap across generations; expenditure; fear; spending behavior